Let's Talk Sex: A Pilot Study of Sexual History Elicitation by Providers of STD Services in Leon County, Florida - Salimah El-Amin; Sandra Suther; Gebre-Egziabher Kiros; Khaing Zaw (University of North Florida, 2016)
An estimated one million sexually transmitted diseases (STDs) are reported annually in the United States. Florida has some of the highest HIV and STD rates in the country. STDs are a particular problem for minorities, women, and adolescents. Sexual history elicitation is a tool available to clinicians to assess patients' sexual risk behaviors and to counsel, test, and treat STDs. Previous barriers to sexual history elicitation include subject matter, patient -physician communications, provider training, and physician perceptions. This pilot study was designed to test a survey questionnaire that measures primary care provider (PCP) sexual elicitation practices. PCPs included obstetricians and gynecologists, family practitioners, internal medicine physicians, pediatricians, nurse practitioners, and physician assistants in Leon County Florida. Between January 2010 and March 2010 a convenience sample of 50 PCPs in Florida were administered a pencil-and-paper survey. The survey instrument was constructed and tested to measure PCP sexual elicitation practices. The survey instrument was found to be an internally consistent and reliable assessment tool for sexual history elicitation. These preliminary pilot study findings warrant a larger study.